2020
DOI: 10.1089/chi.2019.0238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Gardening and Physical Activity Intervention in Title 1 Schools: The TGEG Study

Abstract: Background: The purpose of the Texas!Grow!Eat!Go! (TGEG) study was to assess individual and combined effects of schoolbased gardening and physical activity (PA) interventions on children's eating and PA behaviors and obesity status. Methods: Using a 2 • 2 design, 28 low-income schools in Texas were randomized to 1 of 4 conditions: (1) School Garden intervention (Learn!Grow!Eat!Go! [LGEG]), (2) PA intervention (Walk Across Texas [WAT!]), (3) both Garden and PA intervention (Combined), or (4) neither Garden nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 58 publications
0
54
1
Order By: Relevance
“…The results showed that there was no significant difference in overweight and obesity intervals between the intervention and control group ( p = 0.8), and subjects’ vegetable intake, intake motivation, and preference in SGA combined with the PA group and the SGA group were significantly improved compared with the control group ( p = 0.3). Alexandra et al [ 55 ] used the same intervention methods as Evans’ [ 54 ] to test the accuracy of the research results. After 24 weeks of intervention, they found that vegetable preference in the SGA combined with PA group, as well as in the SGA group, was significantly improved compared to the control group ( p = 0.013 and p = 0.001, respectively), especially in regard to vegetable taste ( p = 0.000 and p = 0.000, respectively) and nutritional knowledge ( p = 0.033, p = 0.001 respectively)”.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that there was no significant difference in overweight and obesity intervals between the intervention and control group ( p = 0.8), and subjects’ vegetable intake, intake motivation, and preference in SGA combined with the PA group and the SGA group were significantly improved compared with the control group ( p = 0.3). Alexandra et al [ 55 ] used the same intervention methods as Evans’ [ 54 ] to test the accuracy of the research results. After 24 weeks of intervention, they found that vegetable preference in the SGA combined with PA group, as well as in the SGA group, was significantly improved compared to the control group ( p = 0.013 and p = 0.001, respectively), especially in regard to vegetable taste ( p = 0.000 and p = 0.000, respectively) and nutritional knowledge ( p = 0.033, p = 0.001 respectively)”.…”
Section: Resultsmentioning
confidence: 99%
“…Still, these studies were included in this study for meta-analysis. However, the only two studies using SGA combined with PA as the intervention method have included FVs and other obesity-related outcomes [ 54 , 55 ], which were not unified with those outcomes in the other 12 studies. Thus, they can only be included in this study for SR. Our study shows that SGA and SGA combined with PA can effectively increase children’s FVs and improve their fruit and vegetable knowledge, intake motivation, and intake preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study of US elementary schools between 2006 and 2014 found that the prevalence of gardens increased from 11.9% in 2006–2007 to 31.2% in 2013–2014 [ 10 ]. As school garden advocates push for more gardens in schools, they often cite the wealth of direct and indirect benefits that school gardens can have on students, including academic performance, psychosocial factors, dietary intake, mental health, obesity risk factors, and physical activity [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. One of the most commonly reported benefits is an increase in fruit and vegetable intake.…”
Section: Introductionmentioning
confidence: 99%
“…This limits the ability to determine whether causality exists between changes in dietary behaviors and garden-based interventions. The few existing randomized controlled trials (RCTs) have been limited by short duration, intervention intensity and fidelity of implementation, and methods used to assess overall dietary or vegetable intake (e.g., food frequency questionnaires) [ 14 , 18 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%